Monitoring water stress in Mediterranean semi-natural vegetation with satellite and meteorological data - Moreno, a.; Maselli, F; Chiesi, M; Genesio, L; Vaccari, F; Seufert, G; Gilabert, M.a. A (International Journal of Applied Earth Observation and Geoinformation, 2014)
In arid and semi-arid environments, the characterization of the inter-annual variations of the light use efficiency ε due to water stress still relies mostly on meteorological data. Thus the GPP estimation based on procedures exclusively driven by remote sensing data has not found yet a widespread use. In this work, the potential to characterize the water stress in semi-natural vegetation of three spectral indices (NDWI, SIWSI and NDI7) – from MODIS broad spectral bands – has been analyzed in comparison to a meteorological factor (Cws). The study comprises 70 sites (belonging to 7 different ecosystems) uniformly distributed over Tuscany, and three eddy covariance tower sites. An operational methodology, which combines meteorological and MODIS data, to characterize the inter-annual variations of ε due to summer water stress is proposed. Its main advantage is that it relies on existing series of meteorological data characterizing each site and allows calculating a typical Cws profile that can be “updated” (C∗ ws) for the actual conditions using MODIS spectral indices. The results confirm that the modified C∗ ws can be used as a proxy of water stress that does not require concurrent information on meteorological data
Keywords: light use efficiency; Satellite data; Semi-natural vegetation; water stress